1972
DOI: 10.1029/ja077i031p06104
|View full text |Cite
|
Sign up to set email alerts
|

Satellite observations of energetic heavy ions during a geomagnetic storm

Abstract: Large fluxes of energetic heavy ions (M / q ≈ 16) were observed in the inner magnetosphere during the geomagnetic storm of December 17, 1971. The observations were made by a set of energetic‐ion mass spectrometers covering the energy range 0.7–12 kev on board the polar‐orbiting satellite 1971‐089A (800‐km altitude, ≈0300 LT). Significant heavy‐ion fluxes were observed for a period of approximately 48 hours during the main phase of the storm. The heavy‐ion fluxes frequently exceeded the proton fluxes in the 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
286
0
1

Year Published

1975
1975
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 504 publications
(301 citation statements)
references
References 11 publications
3
286
0
1
Order By: Relevance
“…The discoveries of ions in the magnetosphere heavier than hydrogen (Shelley et al, 1972) and ion and electron beams directed up along magnetic field lines from the atmosphere Johnson et al, 1977;McIlwain_, 1975) have suggested that the ionosphere may he a source for ring current particles, rather than, or in addition to, the plasma sheet.…”
Section: Introductionmentioning
confidence: 99%
“…The discoveries of ions in the magnetosphere heavier than hydrogen (Shelley et al, 1972) and ion and electron beams directed up along magnetic field lines from the atmosphere Johnson et al, 1977;McIlwain_, 1975) have suggested that the ionosphere may he a source for ring current particles, rather than, or in addition to, the plasma sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Although some of the early measurements by mass spectrometers in space discovered energetic heavy ions of ionospheric origin (e.g., Shelley et al, 1972;Balsiger et al, 1980), it was relatively recently that the role of ionospheric particles in the ring current evolution during storms became evident after the AMPTE mission (Krimigis et al, 1982). The AMPTE lifetime coincided with the solar minimum, and thus only one great storm was observed.…”
Section: Ionospheric Origin Of Ring Current Particlesmentioning
confidence: 99%
“…In the early 1970s the solar-origin paradigm was challenged by the discovery of energetic heavy ions (i.e., ions with M/q=16) at energies up to 17 keV (Shelley et al, 1972) by the first mass spectrometer in space, on board the polar-orbiting satellite 1971-089A. These ions were presumably O + ions originating in the terrestrial ionosphere.…”
Section: Ring Current Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent low-altitude observations of the composition of positive ions precipitating into the auroral zone suggest that at least part of these plasmas can be attributed to the ionosphere. Shelley, Sharp and Johnson [1972] have reported the convincing discovery of large intensities of energetic oxygen ions during geomagnetic storms. A exemplary set of observations is given in Figure 10.…”
Section: The Low-altitude Plasmasmentioning
confidence: 99%